2023
DOI: 10.15835/nbha51413378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous brassinolide and AM fungi on growth, photosynthetic characteristics and antioxidant enzyme system of Leymus chinensis under salt and alkali stress

Zhanwu GAO,
Jing LIU,
Qian LI
et al.

Abstract: Salinity and alkali stresses are a major abiotic stress negatively affecting crop productivity around the globe. Therefore, it is mandatory to develop the effective measures to mitigate the adverse impacts of these stresses for ensuring sustainable crop productivity and food security. Therefore, a pot experiment determined the effects of brassinolide application, inoculation with AM fungi (Funneliformis mosseae) and their combined use on the growth, photosynthesis and antioxidant system of Leymus chinensis und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A large number of studies have found that inoculating PGPR under saline-alkali stress can reduce the harm of salt stress to plants. The combination of exogenous brassinolide and AM fungi (Funneliformis mosseae) improved the antioxidant enzyme activity of Leymus chinensis under saline-alkali stress, alleviating the toxic effects of saline-alkali stress on plants [34]. Treatment of maize seedlings with Pseudomonas monteilii PN1 significantly promoted the growth of maize seedlings, significantly decreased antioxidant enzyme activity, MDA, and Pro content, and increased the tolerance of maize seedlings to saline-alkali stress [35].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have found that inoculating PGPR under saline-alkali stress can reduce the harm of salt stress to plants. The combination of exogenous brassinolide and AM fungi (Funneliformis mosseae) improved the antioxidant enzyme activity of Leymus chinensis under saline-alkali stress, alleviating the toxic effects of saline-alkali stress on plants [34]. Treatment of maize seedlings with Pseudomonas monteilii PN1 significantly promoted the growth of maize seedlings, significantly decreased antioxidant enzyme activity, MDA, and Pro content, and increased the tolerance of maize seedlings to saline-alkali stress [35].…”
Section: Discussionmentioning
confidence: 99%